KEPERCAYAAN DIRI ATLET PON DIY MENGHADAPI PON XVI DI PALEMBANG - Dimyati Dimyati (Jurnal Penelitian Humaniora, 2004)
Abstract This research aimed to know the level of self-confidence of all the athlete of National Games (PON) of Yogyakarta province (DIY) which is drawn up to face the National Games (PON) XVI in Palembang. The population is all readily athlete National Games (PON) of Yogyakarta Palembang, the amount to 158 athletes coming from 28 athletic branches. The population only 90 athletes coming from 18 athletic branches becoming sample in this research. Technique Sampling used is sample random sampling. Instrument used is “The Sport Confidence Inventory” which has been modified. The result indicated that the mean of all athletes of National Games of (PON) Yogyakarta Special Province (DIY) had the level of self-confidence 73.37% in facing National Games (PON) XVI in Palembang. The concluded that all athletes of the national Games (PON) of Yogyakarta Special province (DIY) had the level of high self confidence in facing of National Games (PON) XVI in Palembang Keywords:self-confidence, athlete, national games